Spatial gradients in snow layering and 10 m temperatures at two EPICA-Dronning Maud Land (Antarctica) pre-site-survey drill sites - Holmlund, P.; Gjerde, K.; Gundestrup, N.; Hansson, M.; Isaksson, E.; Karlöf, L.; Nman, M.; Pettersson, R.; Pinglot, F.; Reijmer, C. H.; Stenberg, M.; Thomassen, M.; et al. (Annals of Glaciology, 2000)
During the 1997/98 field season, Sweden, Norway and The Netherlands performed a pre-site survey for EPICA in Dronning Maud Land, Antarctica. This paper summarizes the results and pays special attention to the high spatial gradients found in snow layering and temperatures. The sites were "Camp Victoria" (CV) on Amundsenisen (76° S, 8° W; 2400 m a.s.l.), approximately 550 km from the coast, and "Camp Maudheimvidda" (CM) on Maudheimvidda (74° S 13° W; 362 m a.s.L), some 140 km from the coast.The drilling programme included both medium-long firn/ice cores and shallow firn cores. These were analysed by means of δ18O, DEP, ECM,β activity, density, and ion content. The combined results suggests a mean annual accumulation rate of 60 mm. we. for CV and 220 mm. we. for CM.Variability measurements of spatial snow layering were performed at two scales; over tens of kilometres by radar and over a few metres by pits and high-resolution radar soundings. Results, as measured by relative standard deviation, were typically 10% on the polar plateau and as high as 50% near the coast.The 10 m temperature measurements were –38.5°C (std dev. = 0.5°) for CV and –17.6°C (std dev.=0.15°) for CM.Snow chemistry was sampled at each medium-long-core drill site. Comparison of δ18O profiles from snow pits and the uppermost part of the CV medium-long core showed large variations. Mean δ18O valuesover 2 m profiles varied between 41.6%, and 39.7%o within a horizontal distance of 50 m.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

A 1500 year record of accumulation at Amundsenisen western Dronning Maud Land, Antarctica, derived from electrical and radioactive measurements on a 120 m ice core - Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Kohler, Jack; Pinglot, Jean Francis; Wilhelms, Frank; Hansson, Margareta; Holmlund, Per; Nyman, M; Pettersson, Rikard; Stenberg, Malin; Thomassen, M P A; et al. (Journal of Geophysical Research: Atmospheres, 2000)
During the Nordic EPICA pre-site survey in Dronning Maud Land in 1997/1998 a 120 m long ice core was retrieved (76°00′S 08°03′W, 2400 m above sea level). The whole core has been measured using the electric conductivity measurement (ECM) and dielectric profiling (DEP) techniques, and the core chronology has been established by detecting major volcanic eruptions. In a nearby shallow core radioactive traces from nuclear tests conducted during the 1950s and 1960s have been identified. Altogether, 13 ECM and DEP peaks in the long core are identified as originating from specific volcanic eruptions. In addition two peaks of increased total β activity are identified in the short core. Accumulation is calculated as averages over the time periods between these dated events. Accumulation rate is 62 millimetres (w. eq./yr) for the last 181 years (1816 A.D. to present) and 61 mm w. eq./yr for the last 1457 years (540 A.D. to present). Our record shows an 8% decrease in accumulation between 1452 and 1641 A.D. (i.e. part of the Little Ice Age), compared to the long-term mean.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; iskjerner; paleoklimatologi

Snow and blue-ice distribution patterns on the coastal Antarctic Ice Sheet - Liston, Glen E.; Winther, Jan-Gunnar; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut; Karlöf, Lars (Antarctic Science, 2000)
Surface patterns of alternating snow and blue-ice bands are found in the Jutulgryta area of Dronning Maud Land, Antarctica. The snow-accumulation regions exist in the lee of blue-ice topographic ridges aligned perpendicular to winter winds. The snow bands are c. 500–2000 m wide and up to several kilometres long. In Jutulgryta, these features cover c. 5000 km2. These alternating snow and blue-ice bands are simulated using a snow transport and redistribution model, SnowTran-3D, that is driven with a winter cycle of observed daily screen-height air temperature, humidity, and wind speed and direction. The snow-transport model is coupled to a wind model that simulates wind flow over the relatively complex topography. Model results indicate that winter winds interact with the ice topographic features to produce alternating surface patterns of snow accumulation and erosion. In addition, model sensitivity simulations suggest that subtle topographic variations, on the order of 5m elevation change over a horizontal distance of 1 to 1.5 km, can lead to snow-accumulation variations that differ by a factor of six. This result is expected to have important consequences regarding the choice of sites for ice-coring efforts in Antarctica and elsewhere.
Keywords: Dronning Maud Land; blåis; geofysikk; glasiologi; iskjerner